(untitled) (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted at the Hill Agricultural Research Station, Khagrachari from June to November 2004 to find out the effect of nitrogen (60, 80, 100 and 120 kg/ha) and phosphorus (80, 100 and 120 kg/ha) on the growth and yield of okra in hill slope condition during rainy season. The highest yield (16.73 t/ha) was obtained from 100 kg N/ha, which was statistically identical to 120 kg per hectare. In case of phosphorus, the highest yield of 15.77 t/ha was obtained from 120 kg P2O5/ha and was closely followed by the dose of 100 kg P/ha (4.73 t/ha). Considering the treatment combinations, the highest yield (19.22 t/ha) was produced by N100P120 and there were no significant variations among N100P100, N120P100 and N120P120. The highest gross return (Tk.193200) and net return (Tk.146l40) were obtained from N100P120. The BCR was also higher (4.08) under the same treatment combination. Key Words: Nitrogen; phosphorus; okra growth; okra yield. DOI: 10.3329/bjar.v34i4.5846 Bangladesh J. Agril. Res. 34(4) : 713-722, December 2009